2008
DOI: 10.1371/journal.pbio.0060237
|View full text |Cite
|
Sign up to set email alerts
|

It's Not How Fat You Are, It's What You Do with It That Counts

Abstract: Mechanisms underlying obesity-related metabolic disorders are poorly understood. Samuel Virtue and Antonio Vidal-Puig explore the evidence for an emerging hypothesis that attributes metabolic complications not to obesity per se, but to an individual's capacity for adipose tissue expandability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
183
0
5

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 260 publications
(191 citation statements)
references
References 33 publications
(39 reference statements)
3
183
0
5
Order By: Relevance
“…This improvement of metabolic flexibility correlated with changes in body weight, adiposity and glycaemic control in accordance with the notion that metabolic flexibility is closely associated with insulin sensitivity [2,32] and that impaired flexibility represents an early defect in the development of type 2 diabetes [35]. Metabolic syndrome is linked to inflammatory changes in both WAT and liver [1]. In this study, in accordance with the previous findings [17,18,21], dietary LC n-3 PUFA supplementation resulted in the inhibition of formation of various LC n-6 PUFA-derived pro-inflammatory eicosanoids in both tissues as well as in the induction of the antiinflammatory molecules.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…This improvement of metabolic flexibility correlated with changes in body weight, adiposity and glycaemic control in accordance with the notion that metabolic flexibility is closely associated with insulin sensitivity [2,32] and that impaired flexibility represents an early defect in the development of type 2 diabetes [35]. Metabolic syndrome is linked to inflammatory changes in both WAT and liver [1]. In this study, in accordance with the previous findings [17,18,21], dietary LC n-3 PUFA supplementation resulted in the inhibition of formation of various LC n-6 PUFA-derived pro-inflammatory eicosanoids in both tissues as well as in the induction of the antiinflammatory molecules.…”
Section: Discussionsupporting
confidence: 84%
“…When (post)prandial plasma levels of NEFA and triacylglycerol (TG) exceed the storage capacity of WAT [1], other tissues including the liver and muscle become overloaded with lipids, which results in insulin resistance, the key event in the pathophysiology of metabolic syndrome [2]. The important role of WAT in energy homeostasis is underscored by the findings that WAT is one of the key organs affected by calorie restriction, the most effective strategy to prolong a healthy life in several species [3], and by the fact that accumulation of body fat can be reduced through upregulation of lipid catabolism in WAT [4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, components of the TNFα and IL-1-β-signalling pathways prevent PPARγ binding to DNA by associating with NF-κB (72) . This (53) . The hypothesis proposes that in positive energy balance, subcutaneous adipose tissue (SAT) has a limited capacity to increase its mass.…”
Section: Adipogenesismentioning
confidence: 87%
“…15 It was suggested that adipose tissue expandability is a more important determinant of obesity-associated metabolic disorders than the absolute amount of adipose tissue an individual possesses. 16 Moreover, larger fat cells are associated with a low-grade adipose tissue inflammation, another key factor linking obesity with insulin resistance. 13,14,[17][18][19] Enhanced secretion of chemoattractants in obese state, like monocyte chemoattractant protein-1 (MCP-1), is believed to promote migration of macrophages 20,21 as well as other immune cells 22 into the tissue accompanied by the phenotypic switch of macrophages to proinflammatory state.…”
Section: Introductionmentioning
confidence: 99%